The Relationship between Reading Interest and Vocabulary Mastery of Fifth-Grade Students of SDN Gempol Sari - Sintawati, Fairus; Nurfitriana, Meida; Nupus, Neng Ana Aprilya (JEDLISH : Journal Of Education and English Language Teaching, 2021)
This study aims to determine the relationship between reading interest and mastery of English vocabulary. This research was conducted on fifth grade students of SDN Gempol Sari, with a sample size of 50 students taken from classes VA and VB. and the technique used to analyze the data is statistical regression and correlation techniques. Data were collected using test instruments for English vocabulary mastery and questionnaires for reading interest which were developed by the researchers themselves and had gone through validation process. The results of the study show (1) there is a significant relationship between reading interest and vocabulary mastery in English. The results of the analysis show the calculated f value of 2.60 is greater than the F-table at the level of significance = 0.05 of 1.64 and = 0.01 of 2.32. 12 is 0.35. 12 of 0.35 or 35%. The results of the regression analysis and the correlation between reading interest and mastery of English vocabulary, obtained the regression equation Y = 11.68 + 0.14X1 + 0.36 X 2Y with a correlation coefficient of 0.35 and the results of the significance test at the confidence level = 0.05 this indicates that reading interest and vocabulary mastery both contributed to the English language of 0.70.